2013
DOI: 10.1111/nph.12610
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversification of duplicated chalcone synthase genes in anthocyanin biosynthesis of Gerbera hybrida

Abstract: SummaryChalcone synthase (CHS) is the key enzyme in the first committed step of the flavonoid biosynthetic pathway and catalyzes the stepwise condensation of 4-coumaroyl-CoA and malonyl-CoA to naringenin chalcone. In plants, CHS is often encoded by a small family of genes that are temporally and spatially regulated. Our earlier studies have shown that GCHS4 is highly activated by ectopic expression of an MYB-type regulator GMYB10 in gerbera (Gerbera hybrida).The tissue-and development-specific expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 106 publications
7
120
0
Order By: Relevance
“…The differential transcript levels of Ga CHSs in different organs was in agreement with the earlier studies on CHS multigene family of Glycine max and Gerbera hybrida [57,63]. The variable expression patterns indicate the efficient selection of Ga CHS isoforms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The differential transcript levels of Ga CHSs in different organs was in agreement with the earlier studies on CHS multigene family of Glycine max and Gerbera hybrida [57,63]. The variable expression patterns indicate the efficient selection of Ga CHS isoforms.…”
Section: Discussionsupporting
confidence: 90%
“…It has been observed that CHS shows wide substrate specificity range as it could accept both aliphatic and aromatic CoA esters to produce various reaction products including the unnatural aromatic polyketide [55]. The differential enzyme activity of different CHS isoforms with different substrates has also been reported in Humulus lupulus [56], Gerbera hybrida [57], Emblica officinalis [58] and others. The differential enzyme activity of Ga CHS2 towards different substrates indicates its evolutionary expansion possibly due to gene duplication “Fig 6”.…”
Section: Discussionmentioning
confidence: 99%
“…It has extended primarily from the model plants to various economically important species, including apple (Malus domestica), grape (Vitis vinifera), potato (Solanum tuberosum), strawberry (Fragaria spp. ), and tomato (Solanum lycopersicum; Deng et al, 2014). However, the limited availability of these beneficial compounds from their natural sources makes flavonoids prime candidates to be synthesized in engineered microbes like Escherichia coli and Saccharomyces cerevisiae .…”
mentioning
confidence: 99%
“…To persist over long periods of evolutionary time, nearly all plant genes are represented within most plant genomes as small to large gene families (Han et al, 2006). For instance, in many angiosperms, CHS is encoded by a multigene family with members ranging from two (Zea mays), three (Gerbera hybrida), six (Ipomoea purpurea), seven (Pisum sativum), eight (Physcomitrella patens), nine (Glycine max), and even 10 in some species like Petunia hybrida (Jiang et al, 2006;Deng et al, 2014). These gene families emerge as a result of selective gene duplication and subsequent nucleotide substitution events.…”
mentioning
confidence: 99%
“…The chalcone synthase (CHS) superfamily of type III polyketide synthases (PKSs) are crucial enzymes responsible for the formation of numerous structurally diverse and biologically significant secondary metabolites, and some of the metabolites can serve as antibiotics, anticancer drugs, and immunosuppressants . CHS and homologous members of type III PKSs are usually homodimers of 40–45 kDa subunits, and they perform a complete series of decarboxylation, condensation, cyclization, and aromatization reactions in a single active site .…”
mentioning
confidence: 99%